SOCEMI: 25 años de investigación al servicio de la salud - Acevedo-Villar, Tania; Carrasco-Farfán, Carlos; Barrios-Borjas, Dayana Alejandra (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2018)
Carta al Editor (Sin resumen)